Sarojini Naidu's select poems, with an introduction, notes, and bibliography for further study - Gupta, A. N. (Prakash Book Depot, 1976)
On the life and works of the Indo-Anglian authoress Sarojini Chattopadhyay Naidu, 1879-1949; a study.